ANALYSIS OF FOREIGN SUPERVISION POLICY THROUGH APLIKASI PELAPORAN ORANG ASING (APOA) IN NON TPI BOGOR I CLASS IMMIGRATION OFFICE) - W Wilonotomo; Koesmoyo Ponco Aji; M Alvi Syahrin (Polteknik Imigrasi, 2020)
Bogor Districts and Bogor City are central tourism areas for International visitors. Various visitors attractions in both regions attract foreign tourists to visit so that the growth of accommodation business also increases. Increasing the growth of accommodation businesses needs to be integrated with foreign reporting applications. This writing aims to analyze the foreign reporting application policy at the immigration office using literature and field observation methods. The writing results show that the number of accommodation businesses is not proportional to the number of reporters. If further reviewed, it is necessary to update the foreign control system policy mechanism and carry out integration between foreign reporting application applications for accommodation business licensing services.